POLPA CELULÓSICA DE BAMBU PRODUZIDA PELO PROCESSO ETANOL/ÁGUA PARA APLICAÇÕES DE REFORÇO - Correia, Viviane Da Costa; Curvelo, Antonio Aprigio da Silva; Marabezi, Karen; Almeida, Alessandra Etuko Feuzicana De Souza; Savastano Junior, Holmer (Ciência Florestal, 2015)
http://dx.doi.org/10.5902/1980509817470 Organosolv pulping is the clean chemical process of using organic solvents to aid in the removal of lignin and hemicellulose from lignocellulosic raw materials. This method provides facility for solvent recovery at the end of the process. In this work, it was to produce bamboo cellulosic pulp by the organosolv process evaluating different temperatures and reaction times, and the pulps were analyzed aiming their future application in the reinforcement of composites. The production of bamboo pulp by the organosolv process was studied varying the cooking conditions at 1, 2 and 3 h and 150, 170 and 190oC of temperature, in order to achieve the ideal conditions of yield, chemical and morphological characteristics of the pulp for its potential application in the reinforcement of composites. The best results for delignification (kappa number of 38), with relatively lower fiber degradation (viscosity of 625 cm3 g-1), aspect ratio of 40.4 and the index zero-span of 204 Nm g-1, were achieved for the pulping process at 190oC for 2 h. These pulping conditions can be considered as the more appropriate in the range of time intervals evaluated in this work. The higher mechanical strength and the lower incidence of morphological defects in the fiber (6.0% of curls and 10.6% of kinks) can demonstrate the potential of organosolv bamboo pulp as a reinforcing element.